The problems reported by cancer patients with major depression. - Kleiboer, A; Bennett, F; Hodges, L; Walker, J; Thekkumpurath, P; Sharpe, M (2011)
OBJECTIVE: To describe the problems reported by people with cancer and major depressive disorder as elicited before starting problem-solving therapy (PST). METHODS: Ninety-eight outpatients, with a variety of cancers who met criteria for major depression, received PST as part of a system of treatment called 'Depression Care for People with Cancer' within a randomized trial. During the first session of PST, each patient was asked to provide an exhaustive list of problems defined as 'anything that was bothering them'. A coding system, based on thematic content, was developed to categorize the problems listed. Each problem was then coded by two raters independently (κ=0.81). The resulting categories were organized into larger conceptual domains using a card-sorting task. RESULTS: Thirty-six problem categories were generated which were in turn organized into 11 larger conceptual domains. Patients reported problems in a mean of 9.2 different categories (range 3-21) and 5.7 domains (range 2-9). The most common problem categories were 'concerns about other people's well-being' (65%), 'problems in interpersonal relations' (61%), 'loss of interest' (56%), 'low mood' (55%), and 'cancer recurrence or relapse' (54%). CONCLUSIONS: People with cancer and major depression report a wide variety of problems that include, but go beyond concerns about, both cancer and depression. The large number of problems related to concerns about other people's well-being and difficulties in interpersonal relationships, stresses the importance of these topics to patients and should be given more weight in the assessment and management of depressed cancer patients.